Accidental intestinal wounds in gynecological sugery using the abdominal approach - di Giovanni Bruno, Juan; Altier Castromán, Humberto (Cirugía del Uruguay, 1977)
Out of a total of 1. 203 gynecological interventions using the abdominal approach, performed at the "Hospital de Clínicas" (University Hospital) in the period 1970-75, there were 6 cases of accidental intestinal wounds. Four of them occurred in coordination surgery and two in urgency surgery. Intestinal sectórs involved were: small intestine (2 cases), sigmoid colon ( 1 case) and rectum ( 3 cases). Intraoperatory diagnosis of this complication was made in 5 cases, with immediate repair. Satisfactory results were obtained in two cases, while the remainer underwent hazardeous evolution and involved prolonged average hospitalization ( 100 days), although no deaths occurred in this series.